2021
DOI: 10.1038/s41598-021-99411-9
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the cereal leaf beetle (Oulema melanopus) microbiome depends on the insect’s developmental stage, host plant, and origin

Abstract: Cereal leaf beetle (CLB, Oulema melanopus, Coleoptera, Chrysomelidae) is a serious agricultural pest that causes considerable damages to agricultural production. The aim of this study was to characterize the bacterial communities associated with larvae and imagoes of CLB collected from various cereal host species and locations. The bacterial profile was characterized by 16S rRNA gene sequencing at the V3-V4 hypervariable region. Using taxonomy-based analysis, the bacterial community of CLB containing 16 phyla,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…The manipulative experiment showed that larvae fed with L. lactis before chlorpyrifos treatment had a five‐fold lower mortality rate. Lactococcus lactis is a member of the lactic acid bacteria that are commonly associated with the microbiomes of insects, 66 contributing to the digestion of polysaccharides and sucrose 61,67–69 . This provides two possible explanations for our findings: (i) L. lactis degraded chlorpyrifos or (ii) it provided nutrients to the host to overcome pesticide stress.…”
Section: Discussionmentioning
confidence: 78%
“…The manipulative experiment showed that larvae fed with L. lactis before chlorpyrifos treatment had a five‐fold lower mortality rate. Lactococcus lactis is a member of the lactic acid bacteria that are commonly associated with the microbiomes of insects, 66 contributing to the digestion of polysaccharides and sucrose 61,67–69 . This provides two possible explanations for our findings: (i) L. lactis degraded chlorpyrifos or (ii) it provided nutrients to the host to overcome pesticide stress.…”
Section: Discussionmentioning
confidence: 78%
“…Chung et al [ 16 ] have indicated that Wolbachia may play a key role in shaping the tomato plant’s defensive response to CPB feeding. We have previously indicated that at least 90% of the CLB populations tested are associated with Wolbachia and Rickettsia [ 12 ], which may suggest that the above-mentioned genera of bacteria may have a significant impact not only on the insect host but also on the plant defense response. Therefore, the main aim of this study was to check how the bacteria associated with the CLB larvae modulated the wheat’s response upon larvae feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, herbivorous insects are associated with a wide variety of microorganisms, including bacteria. The CLB is known to be associated with a whole range of bacteria (such as those belonging to the Acinetobacter , Stenotrophomonas , Streptococcus , Serratia , Moraxella , Lactobacillus , Pseudomonas , and Pantoea genus), and their composition can be influenced by various factors, including diet [ 12 ]. However, regardless of the variables analysed (developmental stage, cereal host species and locations from which insects were collected), at least 90% of the tested CLB insects were associated with bacteria belonging to the genera Wolbachia and Rickettsia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NGS analysis of plant DNA was performed to assess if the microbiome composition of bacteria-treated plants differs from the microbiome of the control group treated with water. We used the methodology previously described [ 21 ]. The plant DNA extraction process was verified against the presence of 16S rDNA using bacterial universal primers [ 66 ], and against the presence of commonly reported [ 67 ] contaminations in NGS projects (e.g., with Cutibacterium acnes ) using the nested-PCR technique [ 68 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bacteria-insect relationships are complex and among positive interactions involve both commensalism and mutualism [ 18 ]. The internal diversity of the insect microbiome is related to a variety of gut structures and compartments, various pH levels, redox potential, digestive enzymes [ 19 , 20 ], and insect food [ 21 ]. The studies show that there is a relationship between gut structure and variation of the microbiome.…”
Section: Introductionmentioning
confidence: 99%